Multiple Intestinal Fistulization Managed With Vacuum Therapy - Sandro Cilindro de Souza, PhD; Diego de Almeida Meneses (Plastic and Reconstructive Surgery, Global Open)
Summary:. Intestinal fistulas are disorders of renewed interest due to their rarity, high morbidity and mortality, and difficult treatment. Their incidence has increased due to the use of surgical procedures that leave the abdomen open because of the difficulty in approximating the wound edges. In the last decade, favorable results from the use of vacuum therapy in the management of fistulas have encouraged more research on the subject. This report aimed to analyze the effects of negative pressure wound therapy applied to a patient with multiple intestinal fistulas. A 47-year-old man with 3 complex postoperative fistulas was treated with negative pressure wound therapy. The case evolved with control and reduction of effluxes, reconfiguration of fistulas, granulation, cleaning, and reduction of the associated surgical wound. Negative pressure wound therapy proved effective in controlling the fistulas and optimizing the surgical wound.